Treat-to-target of Gouty Arthritis at Rak-Kor Clinic Nongkhai Hospital - mangkala, jintara (Journal of The Department of Medical Services, 2022)
Background: Gout is the most common inflammatory arthritis worldwide. In the past 20-30 years, there has been a tendency to find more patients worldwide. As in Asia, where the number of cases is rapidly increasing in China, Thailand, South Korea, and Taiwan, there are still many problems in terms of diagnosis and treatment. Objective: To determine the factors related to the targeted treatment of gouty arthritis which uric acid levels were less than 5.0 mg/dL in patients with tophi and less than 5.5 mg/dl in patients without tophi. Methods: The present study method was descriptive by collecting retrospective data of patients with gouty arthritis, ICD 10 M100-109 code, who received treatment at Rak-Kor Clinic, Nongkhai Hospital between 1st July 2010 and 31st December 2020. The factors involved in the treat-to-target of gouty arthritis were analyzed by chi-square test or Fisher’s exact test, and multiple logistic regression (95% CI, p<0.05). Results: Of eligible 585 patients, 94.0% and 90.4% of patients achieved the target uric acid level at one year and throughout the treatment period, respectively. The factors associated with achieving treat-to-target for gouty arthritis with the first 1-year were glomerular filtration rate before treatment ≥ 60 ml/min/1.73 m2 (p=0.024, adjusted OR 2.548, 95% CI 1.133, 5.726) and no drug discontinuation (p=0.011, adjusted OR 2.652, 95% CI 1.245, 5.649). The factors associated with achieving treat-to-target for gouty arthritis throughout the treatment period were body mass index ≤ 25 kg/m2 (p=0.012, adjusted OR 0.355, 95% CI 0.158, 0.797), absence of tophi (p=0.022, adjusted OR 2.172, 95% CI 1.120, 4.211), glomerular filtration rate before treatment ≥ 60 ml/min/1.73 m2 (p=0.001, adjusted OR 3.493, 95% CI 1.639, 7.447), and no drug discontinuation (p=0.039, adjusted OR 2.056, 95% CI 1.037, 4.079). Conclusion: Assessment of the presence of tophi, body mass index, glomerular filtration rate before treatment, and the patient’s regular medication intake will help in planning the treatment and increasing the patient’s target uric acid level.